2021
DOI: 10.1007/s10712-021-09639-3
|View full text |Cite
|
Sign up to set email alerts
|

Review of Relationships Between Solar Wind and Ground-Level Atmospheric Electricity: Case Studies from Hornsund, Spitsbergen, and Swider, Poland

Abstract: This paper reviews individual cases of the relationships between variations of solar wind parameters and variations of the DC vertical atmospheric electric field, $$E_z$$ E z , and current density, $$J_z$$ J z , measured at ground level in the Arctic, at the S. Siedlecki Polish Polar Station Hornsund, Spitsbergen (Svalbard, Norway), and at the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 135 publications
1
8
0
Order By: Relevance
“…Among the few attempts to demonstrate correlated variations in PG records on a global‐scale, Michnowski et al. (2021) examined the correspondence between PG records from Hornsund station (in the Spitsbergen) and from the SWI station on individual days and also statistically in the time period 2004–2011. They concluded that the high correlation between these stations is “seldom”.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the few attempts to demonstrate correlated variations in PG records on a global‐scale, Michnowski et al. (2021) examined the correspondence between PG records from Hornsund station (in the Spitsbergen) and from the SWI station on individual days and also statistically in the time period 2004–2011. They concluded that the high correlation between these stations is “seldom”.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the PG depends on the global state of the DC GEC (Aplin & Harrison, 2014) but it is still unclear how large a global change in the DC GEC must be in order for it to be in fact detectable globally in measured PG time series. On the hourly time scale, possible traces of space weather events has been sought in PG records (Kleimenova et al., 2008; Michnowski et al., 2021; Smirnov, 2014), most notably in association with solar proton events (Nicoll & Harrison, 2014; Tacza et al., 2018) and Forbush decreases (Märcz, 1997; Sheftel et al., 1992). Contribution of these events to the GEC is difficult to detect on a global scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This restriction limited the amount of available data. Michnowski et al (2021) used FW PG values with at least 12 hours of fair weather conditions. In this work we increase the amount of data taking in account every FW hourly value to calculate the diurnal and seasonal variation.…”
Section: Overview Of Fair-weather Pg and Cn Datamentioning
confidence: 99%
“…Previous analyses of the diurnal variation of the PG indicate that Świder is characterised by the double oscillation prevalent in the summer (Northern Hemisphere summer), and the single oscillation in the winter. Furthermore PG values in winter are of higher average amplitude, explained by the higher emissions of anthropogenic aerosols affecting the local electric conductivity (Warzecha, 1976;Kubicki et al, 2003Kubicki et al, , 2007Michnowski et al, 2021). This is rather a typical behaviour of the PG at a rural land station (Israël, 1973a).…”
mentioning
confidence: 99%